Socio-technical scales in socio-environmental modeling: Managing a system-of-systems modeling approach. (January 2021) - Iwanaga, Takuya; Wang, Hsiao-Hsuan; Hamilton, Serena H.; Grimm, Volker; Koralewski, Tomasz E.; Salado, Alejandro; Elsawah, Sondoss; Razavi, Saman; Yang, Jing; Glynn, Pierre; Badham, Jennifer; Voinov, Alexey; et al.
Abstract: System-of-systems approaches for integrated assessments have become prevalent in recent years. Such approaches integrate a variety of models from different disciplines and modeling paradigms to represent a socio-environmental (or social-ecological) system aiming to holistically inform policy and decision-making processes. Central to the system-of-systems approaches is the representation of systems in a multi-tier framework with nested scales. Current modeling paradigms, however, have disciplinary-specific lineage, leading to inconsistencies in the conceptualization and integration of socio-environmental systems. In this paper, a multidisciplinary team of researchers, from engineering, natural and social sciences, have come together to detail socio-technical practices and challenges that arise in the consideration of scale throughout the socio-environmental modeling process. We identify key paths forward, focused on explicit consideration of scale and uncertainty, strengthening interdisciplinary communication, and improvement of the documentation process. We call for a grand vision (and commensurate funding) for holistic system-of-systems research that engages researchers, stakeholders, and policy makers in a multi-tiered process for the co-creation of knowledge and solutions to major socio-environmental problems. Highlights: Scale incompatibilities among system representations are a key challenge in socio-environmental systems modeling. Issues of scale arise from the complexity, size and heterogeneity of the constituent systems and their interactions. A more holistic systems-of-systems modeling framework is needed within which to integrate current approaches and tools. Socio-technical considerations for system-of-systems modeling is presented from a range of disciplinary perspectives.